Total Eosinophils, Ecp And IL-5 In Peripheral Blood During Treatment with Inhaled Corticosteroids in Patients with Asthma - Dimitrievska, Deska; Zdraveska, Marija; Todevski, Dejan (Македонско лекарско друштво = Macedonian Medical Association, 2015)
Introduction. The main attribute of asthma is inflammation, which leads to airway remodeling, bronchial hyperreactivity and reversible or partly reversible airway obstruction. According to GINA, asthma is a chronic inflammatory disorder of the airways in which many cells play a role, in particular mast cells, eosinophils (Eo), and T lymphocytes. Many cells and mediators take part in creating the asthmatic inflammatory reaction, but eosinophils play a central role. The aim of this study was to show the values of biological inflammatory markers (IL-5 and Eo).Methods. Patients with severe asthma, 22 (73.33%) female and 8 (26.66%) male, aged 18-65 years were included in the study. The mean age was 35.30 ±9.65 years. Patients were treated with spray Beclomethasone dipropionate of 250 μg at doses from 1000 to 2000 μg/per day.Results. This study included 30 patients of the University Clinic of Pulmology and Allergology, Skopje, with confirmed bronchial asthma, treated with ICS. In all of the patients we monitored Eo count, ECP and IL-5 in peripheral blood at the beginning of the study, after 2 and 6 months treatment. During treatment with ICS we registered changes in all of the tested parameters.Conclusion. ICS objectively suppress the inflammatory reaction in asthma and the biological markers (IL-5, Eo and ECP), which we have monitored, can measure the accomplished effect. They could be used in everyday practice, not only as diagnostic parameters but also as valid therapeutic guides in treatment of asthma.
Вкупни еозинофили, еозинофилен катјонски протеин (ЕКП) и интерлеукин 5 (ИЛ-5) во периферна крв во тек на третман со инхалаторни кортикостероиди кај пациенти со астма
Keywords: asthma; treatment; Eo count; IL-5; ECP